Reflectivity kinetics of saturable absorbers for laser mirrors. (17th December 2015) - Rubtsova, N N; Borisov, G M; Gol'dort, V G; Kovalyov, A A; Ledovskikh, D V
Abstract: The reflectivity kinetics of saturable absorbers based on semiconductor quantum wells was investigated with differential reflectivity accuracy by the pump–probe technique for energy fluxes (0.27–5.40) photons cm −2 using a femtosecond Yb 3+ :KY(WO4 )2 laser. Three kinds of saturable absorbers were investigated: absorbers based on multiple quantum wells with nano-structured barriers grown over a mirror; the same absorber grown over the substrate; absorbers on multiple quantum wells separated by thick barriers grown over the substrate. The substrate contribution gives a stationary background and a two-photon absorption peak for small probe delays, which complicates the kinetics of the samples grown over the substrate. For absorbers grown over the mirror two exponential decays with a short relaxation time –0.4 ps and with a long relaxation time ps were obtained. The last relaxation time is remarkably shorter than in quantum wells with thick barriers.